Electrospun nanofibers and their potential in dental applications: an updated review - Portillo, Fernando Rosas López; Urias, Aurea Elizabeth Valle; Arredondo, Tonantzin González; Beltran, Marco Antonio Quiroz; Aguilar, Jose Aurelio Cortina; Guerrero, Felix Manuel Manjarrez; Camacho, María del Rosario Cázarez; López, Karely Rojo; Ham, Alfredo del Rosario Ayala; Castro, Ramsés Eduardo Sandoval; Urióstegui, Cristhal Duque; Treviño, Alan I. Valderrama (International Surgery Journal, 2025)
The use of Electrospun nanofibers has proven to be an innovative technology with great potential in the field of dentistry, particularly in tissue engineering and the regeneration of oral and dental tissues. Their ability to mimic the extracellular matrix facilitates cell adhesion, nutrient transport, and cell proliferation, optimizing the biological response. However, despite their multiple benefits, some disadvantages have been reported, related to their structural composition or the difficulty in obtaining ultrafine fibers. Direct electrospinning techniques have been proposed to optimize parameters and incorporate biomolecules. The continuous advancement in biomaterials research will enable better clinical applications and the consolidation of dental tissue regeneration.